The Specificity of Cognitive-Motor Dual-Task Interference on Balance in Young and Older Adults - Ward, Nathan; Menta, Alekya; Ulichney, Virginia; Raileanu, Cristiana; Wooten, Thomas; Hussey, Erika K.; Marfeo, Elizabeth (Frontiers in Aging Neuroscience, 2022)
Standing upright on stable and unstable surfaces requires postural control, and postural control declines as humans age, presenting greater risk of fall-related injury and other negative health outcomes. Secondary cognitive tasks can further impact balance, which highlights the importance of coordination between cognitive and motor processes. Past research indicates that this coordination relies on executive function (EF;the ability to control, maintain, and flexibly direct attention to achieve goals), which coincidentally declines as humans age. This suggests that secondary cognitive tasks requiring EF may exert a greater influence on balance compared to non-EF secondary tasks, and this interaction could be exaggerated among older adults. In the current study, we had younger and older adults complete two Surface Stability conditions (standing-upright on stable vs unstable surfaces) under varying Cognitive Load; participants completed EF (Shifting/Inhibiting/Updating) and non-EF (Processing Speed) secondary cognitive tasks on tablets, as well as a single task control scenario with no secondary cognitive task. Our primary balance measure of interest was sway area, which was measured with an array of wearable inertial measurement unit sensors. Replicating prior work, we found a main effect of Surface Stability with less sway on stable surfaces compared to unstable surfaces, and we found an interaction between Age and Surface Stability with older adults exhibiting significantly greater sway selectively on unstable surfaces compared to younger adults. New findings revealed a main effect of Cognitive Load on sway, with the single task condition having significantly less sway than two of the EF conditions (Updating/Shifting) and the non-EF condition (Processing Speed). We also found an interaction of Cognitive Load and Surface Stability on postural control, where Surface Stability impacted sway the most for the single task and two of the executive function conditions (Inhibition/Shifting). Interestingly, Age didn't interact with Cognitive Load, suggesting that both age groups were equally impacted by secondary cognitive tasks, regardless the presence/type of secondary cognitive task. Taken together, these patterns suggest that cognitive demands vary in their impact on posture control across stable versus unstable surfaces, and that EF involvement may not be the driving mechanism explaining cognitive-motor dual-task interference on balance.